Study of dielectric and physiochemical propertiesof soil at Bastar region of India - Vijay Sahu, Ashutosh Pandey, Tulika Dewangan (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the upcoming awareness for different soil types and its impact on various physical, chemical properties and holding capacity, it is critical to investigate the impact of inorganic materials on soil dielectric potential at microwave frequencies. In this regard, different soil specimens were gathered from varioussites of Dantewada district around NMDC Dantewada agricultural land (Villages- Kirandul, Bade- Bacheli, Bacheli,Bhanshi). Surprisingly, not much has been reported towards the chemical propertiesof the key constituents of these different soils. In the present study, we therefore investigated the different properties of soils, particularly to the dielectric potential from different locations, at microwave frequency. The data revealed the sensitivity towards various soil types and thus helped in determining the soil texture. Furthermore, by knowing the electrical conductivity and dielectric potential of soil samples, various chemical parameters including the different percentages of clay, slit and different physical properties were thus explored.These findings concluded that at different locations, there is remarkable variation in physical and chemical properties of soils. Also, the observed values of soil dielectric characteristics are in good accord with previous research. As a result, researchers working in the field of agriculture might benefit from these characteristics.